The Effect of Marketing Mix on Patient Retention at the Regional General Hospital (RSUD) Datu Beru Takengon - Rizki Anjar Pinanggih; Irwan Saputra; Said Usman; Muhazar Muhazar; Martunis Martunis (Budapest International Research and Critics University, 2022)
Retention of patients as hospital customers is very important for agencies that provide services, in this case hospitals, but is often neglected. Several studies have stated that patient retention can be improved with the existence of a marketing mix by the hospital management. This type of research is observational using a cross sectional design. The population in this study included inpatients at Datu Beru Takengon Hospital where the sample size was determined by the Slovin equation and 113 people were selected. Statistical analysis used was logistic regression. The results showed that there was an effect of the dimensions of the product (product), place (place), health workers (people) and the service process (process) on patient retention in RSUD Datu Beru Takengon (p≤0.05). There is no influence of the dimensions of promotion (promotion) and physical appearance (physical) on patient retention in RSUD Datu Beru Takengon (p>0.05). Based on the results of the study, it can be concluded that the most dominant factor in patient retention at RSUD Datu Beru Takengon is the service process